2008
DOI: 10.1002/jbm.a.31878
|View full text |Cite
|
Sign up to set email alerts
|

Design and characterization of a novel chitosan/nanocrystalline calcium phosphate composite scaffold for bone regeneration

Abstract: To meet the challenge of regenerating bone lost to disease or trauma, biodegradable scaffolds are being investigated as a way to regenerate bone without the need for an auto- or allograft. Here, we have developed a novel microsphere-based chitosan/nanocrystalline calcium phosphate (CaP) composite scaffold and investigated its potential compared to plain chitosan scaffolds to be used as a bone graft substitute. Composite and chitosan scaffolds were prepared by fusing microspheres of 500-900 microm in diameter, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
120
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(137 citation statements)
references
References 49 publications
5
120
1
Order By: Relevance
“…These composite materials have been thoroughly characterized by physicochemical techniques and have been found to contain nanosized hydroxyapatite with structural features close to those of biological apatites. A further development of this approach was pursued by Chesnutt et al, who developed microsphere-based chitosan-nanocrystalline calcium phosphate composite scaffolds [26].…”
Section: Introductionmentioning
confidence: 99%
“…These composite materials have been thoroughly characterized by physicochemical techniques and have been found to contain nanosized hydroxyapatite with structural features close to those of biological apatites. A further development of this approach was pursued by Chesnutt et al, who developed microsphere-based chitosan-nanocrystalline calcium phosphate composite scaffolds [26].…”
Section: Introductionmentioning
confidence: 99%
“…11,16 HA and b-TCP have drawbacks such as their degradation or dissolution rates are difficult to be predicted. Highly sintered HA is non-degradable.…”
Section: Resultsmentioning
confidence: 99%
“…It is biocompatible, biodegradable, renewable, non-toxic, can be fabricated into various forms, has been shown to support the attachment and growth of osteoblasts in vitro and has been widely applied in biomedicine. [9][10][11] Furthermore, as a foreign object, Ch is not rejected from the body. 9 However, Ch is relatively weak and unstable and swells in solution.…”
Section: Introductionmentioning
confidence: 99%
“…This suggested that the chitosan predominant scaffolds were brittle in nature, whereas, incorporation of PLLA within the scaffolds increased the ductility of the scaffolds. [34,35] was totally subsided. The PLLA containing scaffolds exhibit the peak intensity of the peak at ~17° 2θ, which further increased with the increase in the PLLA concentration (with an exception of F5).…”
Section: Mechanical Analysismentioning
confidence: 98%